The problem of personal development of employees of the state employment service of Ukraine: Проблема особистісного розвитку працівників державної служби зайнятості України - Vlasova, Olena; Kalenichenko, Katherine (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
In the article the analysis of modern researches of the personality of employees of the state employment service has been carried out. The psychological aspects of the lack of desire for self-development and self-knowledge of employees of the State Employment Service of Ukraine are described. The 53 persons (38 of which have no higher education) are retraining at psychologist at the Institute of Personnel Training SESU) took part in the research. The revealed factors that have an influence on the indicator of personal self- development of the employees of the SESU: orientation in time, creativity and plasticity of behavior, empathy, emotional management, taking responsibility for their emotions, motivating achievement.
Keywords: personal development; innovative education; permanent education; motivation of achievement; educational self-efficacy